2016
DOI: 10.1016/j.jaim.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Azadirachta indica ameliorates cardiorenal dysfunction through reduction in oxidative stress and extracellular signal regulated protein kinase signalling

Abstract: BackgroundAzadirachta indica is widely distributed in Africa, Asia and other tropical parts of the world. A. indica (AI) is traditionally used for the treatment of several conditions including cancer, hypertension, heart diseases and skin disorders. Intestinal ischaemia-reperfusion is a common pathway for many diseases and may lead to multiple organ dysfunction syndrome and death.ObjectiveIn this study, we investigated the ameliorative effects of AI on intestinal ischaemia-reperfusion injury-induced cardiorena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Laha and Ezeigwe et al demonstrated that Gymnema sylvestre and extract of A. indica have pancreatic islet regeneration properties in diabetic mice 13,19 . The potential effects observed when using these extracts can certainly be ascribed to cellular mechanisms, which include scavenging of free radical, DNA repair, cell cycle alteration, programmed cell death mitigation, and the ability to modulate various signaling pathways 28,29 .…”
Section: Fig 6: Representative Images Of Cell Cycle Analysis Using Fl...mentioning
confidence: 99%
“…Laha and Ezeigwe et al demonstrated that Gymnema sylvestre and extract of A. indica have pancreatic islet regeneration properties in diabetic mice 13,19 . The potential effects observed when using these extracts can certainly be ascribed to cellular mechanisms, which include scavenging of free radical, DNA repair, cell cycle alteration, programmed cell death mitigation, and the ability to modulate various signaling pathways 28,29 .…”
Section: Fig 6: Representative Images Of Cell Cycle Analysis Using Fl...mentioning
confidence: 99%
“…Increase in glutathione levels, better activity of the enzyme G-6-PD. X [3] Bark Powdered bark (20 g). Showed ethanolic extract has the highest content of flavonoids and phenols.…”
Section: Anti-inflammatory Undefinedmentioning
confidence: 99%
“…In a similar fashion, nitric oxide levels were maintained (control 0.036 mole/l, extract 0.034 mole/l and vit c 0.042 mole/    l), but diminished for the IIRI (0.025 mole/l).  Furthermore, levels of GSH were increased resulting in high recovery of the glucose-6-phosphate dehydrogenase (G6PD), therefore boosting the body's natural defenses [3]. Furthermore, studies by Ghatule et al, used acetic acid to induce colitis in rats.…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…34 The potential effects that are seen when using A. indica extracts can positively be attributed to cellular and molecular mechanisms, which comprise detoxication, free radical scavenging, DNA repair, immune surveillance, programmed autophagy and cell death mitigation, cell cycle alteration, anti-inammatory, anti-metastatic and antiangiogenic activities and the capability to modulate different signaling pathways. 35,36 The anti-inammatory activity of NLP is due to the presence of the bioactive compound limonoid. 37,38 This research article addressed the fabrication of costeffective and eco-friendly bio-composites based on sulfatedcarboxymethyl cellulose (S-CMC) and the A. indica leaves (NLP) through a simple and green chemical approach.…”
Section: Introductionmentioning
confidence: 99%